Hazy histories: Smoking atmospheres in twentieth-century Britain - Marković, Ivan (2020)
This thesis is an epistemological experiment in knowing the past atmospherically. It seeks to address the question of how we might go about recovering, from the historical record, something as hazy, fleeting and potentially intangible as an atmosphere. The thesis tells a story of smoking at four key moments in twentieth century British history: the turn of the 20th century, the Second World War, the 1980s, and lastly, the mid-2000s. The story is narrated through the lens of atmosphere to tease out and foreground the feelings, emotions, senses, rhythms and affects that otherwise remain a backdrop in conventional historical accounts.